ANALISIS MANAJEMEN PEMBIAYAAN PADA LEMBAGA KSPPS BMT AR-ROHMAH BANDONGAN MAGELANG - Rochison, Muhammad; Fitriyani, Yeny; Purwanto, Purwanto; Rifki, Muhammad; Hidayat, Yahya Nur (Journal of Sharia Economics, 2024)
Shariah Savings and Credit and Finance Cooperatives (KSPPS) are microfinance institutions that collect and distribute assets to people who need these funds. This research aims to find out the financial management and internal and external systems in KSPPS BMT Ar-Rohmah Bandongan Magelang; this research uses a descriptive qualitative approach with interview techniques, primary and secondary data collection, and documentation. Using SWOT analysis, we can find the weaknesses, strengths, threats, and opportunities in KSPPS Ar-rohmah institution. The results of this study show that the management system in KSPPS BMT Ar-rohmah institution uses a Sharia financing system and has Sharia principles, as well as having several opportunities and weaknesses and threats for institutions; KSPPS BMT Ar-rohmah mitigates risks by paying attention to character, capacity, capital, collateral and economic conditions in customers.